MENINGKATKAN SIKAP PEDULI LINGKUNGAN MELALUI EKSTRAKURIKULER KEPRAMUKAAN PADA SISWA KELAS V SD NEGERI GONDANGDIA 01 PAGI JAKARTA PUSAT - Bella Aprillianti; Endang Wahyudiana; Iva Sarifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This classroom action research aims to improve environmental care attitudes through extracurricular scouting in class V scouts. The research was conducted at SD Negeri Gondangdia 01 Pagi in Central Jakarta. The subjects of this research were VA class students totaling 29 people. The classroom action research model used was the Kemmis and McTaggart model. Research data collection techniques include questionnaires, observation, and documentation. The pre-cycle data on the environmental care attitude of students is 14%. After being given action, the data on the environmental care attitude of students in the first cycle amounted to 45%, then in the second cycle it increased and had met the success criteria set by reaching 83%. The increase in environmental care attitudes is shown by students diligently cleaning the classroom and school environment, throwing garbage in the trash according to its type, recycling garbage, not using disposable products, doing greening, and others. The conclusion of this research is that the application of scouting extracurricular activities can improve environmental care attitudes in VA class scouts of SD Negeri Gondangdia 01 Pagi in Central Jakarta so that teachers can make scouting extracurricular activities as an alternative to improve environmental care attitudes in elementary school students. Keywords: Scouting Extracurricular, Environmental Care Attitude of Class V Students.